Sequential Approximate Multiobjective Optimization Using Computational Intelligence - Yoon, Min.; Yun, Yeboon; Nakayama, Hirotaka; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book highlights a new direction of multiobjective optimzation, which has never been treated in previous publications. When the function form of objective functions is not known explicitly as encountered in many practical problems, sequential approximate optimization based on metamodels is an effective tool from a practical viewpoint. Several sophisticated methods for sequential approximate multiobjective optimization using computational intelligence are introduced along with real applications, mainly engineering problems, in this book.
Basic Concepts of Multi-objective Optimization -- Interactive Programming Methods for Multi-objective Optimization -- Generation of Pareto Frontier by Genetic Algorithms -- Multi-objective Optimization and Computational Intelligence -- Sequential Approximate Optimization -- Combining Aspiration Level Approach and SAMO -- Engineering Applications.
Keywords: Mathematics; Operations research; Decision making; Computers; Computer science -- Mathematics; Mathematical models; Mathematical optimization; Management science; Mathematics; Mathematical Modeling and Industrial Mathematics; Operations Research, Management Science; Theory of Computation; Operation Research/Decision Theory; Optimization; Discrete Mathematics in Computer Science; Electronic books